Legal Optimization of Digital Tax Administration in Indonesia: Case of Coretax - Sihombing, Jonker (Journal of Law, Politic and Humanities, 2025)
The core issue in Indonesia’s tax system lies in the underperformance of the core tax administration functions managed by the Directorate General of Taxes, particularly registration, reporting, payment, and enforcement. These weaknesses have contributed to low voluntary compliance and inefficient revenue collection in tax authorities. The purpose of this research is to evaluate whether Indonesia’s core tax system aligns with the Absolute Obligation Theory and the fundamental framework of tax administration law, which view taxation as a non-negotiable obligation of citizens in support of public services and national stability. Using a normative juridical method and a comparative approach with other tax administration models, the study identifies persistent shortcomings in Indonesia’s policy design, administrative capacity, and enforcement strategies. The findings reveal that Indonesia has yet to fully implement tax administration principles in a coherent and effective manner. In conclusion, the study suggests that Indonesia should adopt key lessons in legal clarity, digital integration, and institutional governance to build a more efficient tax administration system.